Risks of N95 Face Mask Use in Subjects With COPD. - Sun Young Kyung; Yujin Kim; Hyunjoong Hwang; Jeong-Woong Park; Sung Hwan Jeong (Respiratory Care, 2020)
BACKGROUND: The N95 filtering facepiece respirator (FFR) is the most popular individual protective device to reduce exposure to particulate matter. However, concerns have been raised with regard to its use because it can increase respiratory resistance and dead space. Therefore, this study assessed the safety of N95 use in patients with COPD and air-flow limitation. METHODS: This prospective study was performed at a tertiary hospital and enrolled 97 subjects with COPD. The subjects were monitored for symptoms and physiologic variables during a 10-min rest period and 6-min walking test while wearing an N95. RESULTS: Of the 97 subjects, 7 with COPD did not wear the N95 for the entire test duration. This mask-failure group showed higher British modified Medical Research Council dyspnea scale scores and lower FEV1 percent of predicted values than did the successful mask use group. A modified Medical Research Council dyspnea scale score 6 3 (odds ratio 167, 95% CI 8.4 to >999.9; P 5 .008) or a FEV1 < 30% predicted (odds ratio 163, 95% CI 7.4 to >999.9; P 5 .001) was associated with a risk of failure to wear the N95. Breathing frequency, blood oxygen saturation, and exhaled carbon dioxide levels also showed significant differences before and after N95 use. CONCLUSIONS: This study demonstrated that subjects with COPD who had modified Medical Research Council dyspnea scale scores ≥ 3 or FEV1 < 30% predicted wear N95s only with care.